THE SCIENTIFIC AND INTELLECTUAL ENVIRONMENT AT THE GHAZNAVID COURT AND THE SCHOLARLY ROOTS OF COMPARATIVE RELIGIOUS STUDIES (World Bulletin of Social Sciences, 2026)
This study examines the scientific and intellectual environment of the Ghaznavid court and its role in the formation of early comparative religious studies within the medieval Islamic world
Keywords: religious classification; medieval Islam